Pertanggungjawaban Hukum terhadap Pengangkutan BBM tanpa Izin Usaha - Putri, Yolanda; Handayati, Nur; Borman, Syahrul M. (LPPM Institut Pendidikan Nusantara Global, 2025)
Indonesia, as the world’s largest archipelagic country, possesses a wealth of strategic natural resources, including oil and natural gas, which are vital to the national economy. The phenomenon of unauthorized fuel trading poses systemic risks and economic losses, as reflected in the case of the Palangkaraya District Court Decision Number 228/PID.SUS/2024/PN.PLK. This study aims to analyze the legal accountability of individuals involved in the transportation of fuel without a commercial business license, based on Law Number 22 of 2001 concerning Oil and Natural Gas and Law Number 7 of 2014 concerning Trade, with a particular focus on the judge’s ratio decidendi. The research uses a normative legal method with statutory, conceptual, and case-based approaches. The population includes all legal materials related to the legal responsibility for unauthorized fuel transportation, with the primary sample being Decision Number 228/PID.SUS/2024/PN.PLK, selected through purposive sampling. Research instruments include quotation cards, analytical matrices, and a categorization framework for legal materials, analyzed using a descriptive-analytical qualitative technique. The findings reveal that the defendant, Hengky Nurcholis, was legally proven to have transported 10,000 liters of Pertamina Dex fuel without an official license and was sentenced to a fine of IDR 30,000,000 with a subsidiary imprisonment of two months. The study concludes that violations of fuel licensing regulations constitute criminal acts that threaten the stability of the national energy distribution system and require firm yet proportionate law enforcement through an individualized sentencing approach.